Effect of age and number of seedlings on rice (Oryza sativa) under SRI in rainfed agro-ecosystem - PRADHAN, ADIKANT; DIXIT, ANIL (The Indian Journal of Agricultural Sciences, 2021)
Field experiment was conducted during the kharif 2018-19 at S G College of Agriculture and Research Station, Jagdalpur to evaluate the effect of number of seedlings/hill and their age on growth, yield and nutrient uptake of rice (Oryza sativa L.) under SRI. The 12 treatments combinations of 1, 2 and 3 seedlings/hill, transplanted at an age of 10, 20, 30 and 40 days were laid out in RBD with 3 replications. The seedlings were transplanted in a square pattern at 25cmx25cm spacing. The crop was weeded by cono-weeder twice. The results showed that transplanting 1 and 2 seedlings attained similar growth, yield attributes and yields being significantly higher than 3 seedlings/hill and 7% yield advancement was obtained with transplanting 1 or 2 seedlings/hill over 3 seedlings/hill. Among the seedling ages 10 and 20 days old seedlings resulted in significantly higher growth, yield attributes and yield than 30 and 40 days old seedlings. Twenty one days old seedlings are more easy to handle and produced grain yield as much as 14 days old seedlings, but increased 5.8% and 13.9% more grain yield than 28 and 35 days old seedlings, respectively.